2013
DOI: 10.1371/journal.pone.0056845
|View full text |Cite
|
Sign up to set email alerts
|

Progress Realized: Trends in HIV-1 Viral Load and CD4 Cell Count in a Tertiary-Care Center from 1999 through 2011

Abstract: BackgroundHIV-1 RNA and CD4 cell counts are important parameters for HIV care. The objective of this study was to assess the overall trends in HIV-1 viral load and CD4 cell counts within our clinic.MethodsPatients with at least one of each test performed by the Infectious Diseases Laboratory from 1999 through 2011 were included in this analysis. By adapting a novel statistical model, log10 HIV-1 RNA means were estimated by month, and log10-transformed HIV-1 RNA means were estimated by calendar year. Geometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
3
5
0
Order By: Relevance
“…Our prior examinations of CD4 cell count and viral loads from 1999 to 2011 demonstrated considerable improvement in median CD4 cell count and the percentage of patients with virologic suppression [ 2 ] as also demonstrated elsewhere [ 3 ]. Now, in the era of potent antiretroviral therapy and capacity for genotypic resistance testing to guide therapy, the occurrence of viral rebound may reflect our challenges with retention in care and adherence to antiretrovirals [ 4 ].…”
Section: Discussionsupporting
confidence: 65%
“…Our prior examinations of CD4 cell count and viral loads from 1999 to 2011 demonstrated considerable improvement in median CD4 cell count and the percentage of patients with virologic suppression [ 2 ] as also demonstrated elsewhere [ 3 ]. Now, in the era of potent antiretroviral therapy and capacity for genotypic resistance testing to guide therapy, the occurrence of viral rebound may reflect our challenges with retention in care and adherence to antiretrovirals [ 4 ].…”
Section: Discussionsupporting
confidence: 65%
“…HIV RNA viral load (VL) is a pivotal outcome variable in studies of HIV infected persons. Viral load measures are central to clinical trials of new antiretroviral (ART) therapy regimens [ 1 , 2 ], randomized trials of ART adherence [ 3 ], and observational cohort studies of HIV patients [ 4 12 ]. In addition, VL is a key component of surveillance databases that provide information on the continuum of care of HIV patients [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reports from individual clinics suggest high levels of viral suppression (5), but current large-scale estimates from across the United States are limited. One of the best assessments was from the North American AIDS Cohort Collaboration on Research and Design (NA-ACCORD), which found peak viral suppression of 72%; however, key potential predictors, such as adherence and substance use, were not examined (6).…”
mentioning
confidence: 99%